The Effect of Circuit Training on Increasing Physical Fitness of Class VIII Students of SMPN 1 Metro - Riyan Jaya Sumantri; Mikkey Anggara (International Conference on Science, Education, and Technology, 2022)
Abstrak. In this research, the writer wanted to know the effect of circuit training on increasing physical fitness of class VIII students at SMPN 1 Metro, with a population of 140 students. The sample taken as much as 20% of the population is 30 students. The sampling method is a simple random sample. Exercise activities were carried out for 1.5 months with a frequency of exercise 3 times a week. The circuit training program that was tried was running back and forth with a distance of 4 m with 3 repetitions, putting the ball into the ring trying 5 times the ball entered the ring, running back and forth by observing the sound of the whistle, push ups 15 ", sprinting 30 m , 15” squat jumps. Retrieval of information using the Indonesian physical fitness test which consists of 5 test items, namely the 60 m sprint test, the hanging lift test for male students and the elbow bending test for female students, the 60 second lying down test, the upright jump test, and the distance running test. another 1200 meters for male students and another 1000 meter distance running test for female students. The results of the research show that circuit training activities affect the increase in physical fitness of class VIII students at SMPN 1 Metro. In the test criteria, if the t-count value is greater than the t-table value, then there is a significant effect. In this research, the t-count value is 16.93 and the t-table value is 2.756. Based on the results of the Indonesian Physical Fitness Test that has been carried out and it is known that there is an increase in physical fitness, it can be concluded that circuit training activities affect the increase in physical fitness of class VIII students at SMPN 1 Metro.